Parental Self-Efficacy—A Predictor of Children's Health Behaviors? Its Impact on Children's Physical Activity and Screen Media Use and Potential Interaction Effect Within a Health Promotion Program - Kieslinger, Katrin; Wartha, Olivia; Pollatos, Olga; Steinacker, Jürgen M.; Kobel, Susanne (Frontiers in Psychology, 2021)
Insufficient physical activity (PA) and increased screen media use (SMU) can have detrimental effects on children’s health. Parental self-efficacy (PSE) can act as an important predictor for a healthy upbringing. The aim of this study was to investigate the influence of PSE on children’s PA and SMU. Additionally, a moderating effect of PSE on the intervention effect of the health promotion program “Join the Healthy Boat” was examined. Using a prospective randomized controlled trial, 558 kindergarten children (3.6 years (SD = 0.6)) were examined. Data was collected using parental self-report. A significant influence of PSE on children’s PA (B = 0.33, p = .025) and children’s SMU (B = 0.42, p = .006) was found. The moderating effect of PSE on the intervention effect was neither significantly related to children’s PA (p = .360) nor to children’s SMU (p = .531). This confirms the importance of PSE on children’s health development. Despite the lack of a moderating effect, interventions should also promote healthy activity behaviors and self-efficacy for parents in order to engage children in a healthy lifestyle.